Study on reasons of dropout of EPI vaccination in selected slum area of Dhaka city, Bangladesh (South East Asia Journal of Public Health, 2013)
This cross sectional study carried out at a selected slum in Dhaka city, Bangladesh. The objective of the study was to examine the reasons of dropout of EPI vaccination among the children of slum areas. Mothers having children 11-23 months with history of EPI dropout were included in the study. A total of 128 mothers were interviewed. Out of 128 respondents 32.8% were in the age of 26-30 yrs; 96.9% were married, 65.7% were housewife, 62.5% had 4-6 members in the family, 50.78% had primary education & rest 10.15% had secondary level education. Approximately 53.1% of the husbands of the respondents were day laborers, and 57.8% of the family had a monthly income in range of Tk.  2001-3000. Out of 128 dropout children, 31.2% were in the age group 11-13 moths and 28.2% were in the age group 20 months and above. During the interview, respondents were able to show the EPI Card of their children. The main reasons for dropping out were a lack of awareness to complete the vaccination schedule (25%), and illness of child (21.9%). The other reasons were fear of reaction (9.4%) and business of the mother (9.4%). There is a need to intensify efforts to increase access for immunization, strengthen surveillance and promote health education to reduce the dropouts in slum areas.South East Asia J Public Health | Jan-June 2012 | Vol 2 Issue 1 | 64-67 DOI: http://dx.doi.org/10.3329/seajph.v2i1.15268